Effects of kinesio taping and transcutaneous electrical nerve stimulation combined with active stretching on hamstring flexibility - Adhitya, I P. G. S.; Yu, W.-Y.; Bass, P.; Kinandana, G. P.; Lin, M.-R. (The Journal of Strength and Conditioning Research, 2022)
Active stretching (AS), Kinesio taping (KT), and transcutaneous electrical nerve stimulation (TENS) are frequently used to ameliorate pain and improve the ranges of motion (ROM) of athletes; however, the effectiveness of KT and TENS combined with AS in ameliorating short hamstring syndrome is yet to be determined. In this single-blinded randomized trial, 135 male soccer players with bilateral short hamstring syndrome were assigned to 3 intervention groups—AS, KT + AS, and TENS + AS—through block randomization. Each subject received the intervention twice per week for 4 weeks. The ROM of both legs was assessed through passive knee extension and straight leg raising tests at baseline and the end of the intervention. After the 4-week intervention, significant ROM changes in both legs were detected in the AS (9.5°-18.4°), KT + AS (14.9°-22.4°), and TENS + AS (14.9°-22.3°) groups. Compared with the AS group, both the KT + AS (3.8°-5.7°) and TENS + AS (3.9°-5.7°) groups showed significantly increased ROM in both legs over the intervention period, and no significant differences were observed in ROM changes between the KT + AS and TENS + AS groups. In conclusion, both KT and TENS in combination with AS may increase ROM more than AS alone, and the improvements obtained using KT with AS and TENS with AS may be similar.